Sustaining Aquaculture Development : The Feeds and Feeding Connection - Hashim, Roshada (2005)
Aquaculture has traditionally played a role in ensuring food security for humans and is often a component of rural development programmes to alleviate poverty. In the last three decades, the aquaculture industry has grown at an unprecedented rate stimulated by the increased demand for fish and fishery products as global population awareness of fish as a health food increased and the almost static production from capture fisheries. Indeed, aquaculture has expanded to become the fastest food producing industry in the world and is expected to contribute to more than half of the global fish consumption by 2030 (FAO, 2000).